Morphological diversity and discrimination tools of the non-marine ostracod Cypridopsis silvestrii across temporal and spatial scales from Patagonia - Ramos, Lorena Yésica (2021)
Geometric morphometric methods are powerful tools to discriminate between closely related ostracods taxa as well as to study the relationship between their morphological variations, taxonomy and paleoecology. In this study, valve outline analysis allows the discrimination between the non-marine ostracod C. silvestrii and R. whatleyi juveniles, pointing out differences in the posterior valve area and surface ornamentation. Modern female specimens of C. silvestrii from 23 sites located in a spatial transect (41 to 51 °S) exhibited extensive morphological variability, on the basis of which three morphotypes (acuminated, transitional, subtruncated) were determined. Multivariate analyses showed that acuminated and transitional shapes are not arranged in groups but the subtruncated morphotype, previously described as E. cecryphalium, seems to be associated with low water conductivity (372 µS cm-1), dominant cold (5 oC) and windy (8.6 m s-1) climatic conditions. The fossil cluster which included nine cores spanning the last 15.6 kyr, only covered acuminated and transitional shapes, which may indicate that these lineages might be older than the subtruncated morphotype. In addition, morphological differences between reproduction modes suggested that parthenogenetic females exhibit de posterior margin more acuminate than sexual females. These results set the ground for more precise ecological and paleoenvironmental studies in Patagonia.